2022
DOI: 10.1097/nna.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

Building Nurse Manager Well-being by Reducing Healthcare System Demands

Abstract: The National Academies of Medicine consensus study committee reported that US healthcare workers experience high levels of burnout resulting from external pressures on the healthcare system and the organization of work. Nurse managers are especially susceptible to burnout. This column provides evidence-based strategies to improve the work environment, reduce the burden of job demands, and promote well-being among nurse managers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 10 publications
1
45
0
Order By: Relevance
“…NMs are leaders who have 24/7 or 12/7 responsibility, engaged in initiatives including human resources, clinical practice, financial management, strategy, and others 9 . NMs are pivotal for creating safe and healthy work environments and critical for quality patient outcomes and overall organizational productivity 3,12,13 . Current literature reflects research efforts focused on clinical nurses as compared with NM, related to stress and job satisfaction; thus, this is an opportunity to add new knowledge.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…NMs are leaders who have 24/7 or 12/7 responsibility, engaged in initiatives including human resources, clinical practice, financial management, strategy, and others 9 . NMs are pivotal for creating safe and healthy work environments and critical for quality patient outcomes and overall organizational productivity 3,12,13 . Current literature reflects research efforts focused on clinical nurses as compared with NM, related to stress and job satisfaction; thus, this is an opportunity to add new knowledge.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Since the start of the pandemic, NMs have confronted conflicting demands for their time and energy amplifying their already stressful jobs. 7 Like staff nurses, managers have been asked to do more with less. They often have little time to cultivate the well-being of their staff, 7 something most valued.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…7 Adequate time off often translates to increased engaged. 7,31 The NMPES provides direction for strategies to pursue solutions to many of these issues. Despite petitions from experts to require advanced degrees for such positions, this study also found that fewer than a 3rd of the participants held a master's degree or higher.…”
Section: Practice Implicationsmentioning
confidence: 99%
“…This is a concern because of the inverse relationship that exists between high clinician burnout and worse patient outcomes such as lower satisfaction, higher mortality, and increased hospital‐associated infection rates 8,9 . In response, healthcare organizations have initiated myriad interventions to improve nurses' well‐being, enhance work–life balance, and increase retention; however, these efforts often fall short in enhancing individuals' ability to cope with, adjust to, or recover from day‐to‐day work‐related stressors 10 …”
Section: Introductionmentioning
confidence: 99%
“…8,9 In response, healthcare organizations have initiated myriad interventions to improve nurses' wellbeing, enhance work-life balance, and increase retention; however, these efforts often fall short in enhancing individuals' ability to cope with, adjust to, or recover from day-to-day work-related stressors. 10…”
mentioning
confidence: 99%